Tranformasi Hukum Wasiat Wajibah Ke dalam Sistem Hukum Nasional - Zainul Aziz Nasution; Faisar Ananda Arfa; Ibnu Radwan siddiq Turnip (STIKes Ibnu Sina Ajibarang, 2025)
Wasiat Wajibah is a form of legally mandated bequest granted to specific heirs who, according to Islamic law, do not receive a share of the inheritance or receive an insufficient portion. This concept originally developed in Islamic jurisprudence as a solution for promoting social justice, particularly for grandchildren whose parent (the decedent’s child) had passed away before the testator. The transformation of this concept into Indonesia’s national legal system represents a response by the legal framework to the demand for substantive justice in the context of family and inheritance matters. This study aims to examine the concept of wasiat wajibah in Islamic law, its application within Indonesia’s positive law—particularly as regulated in the Compilation of Islamic Law (Kompilasi Hukum Islam/KHI)—and its transformation into national law. The research employs a normative juridical method, with analysis based on primary legal sources, namely the Compilation of Islamic Law (KHI), especially Articles 171–214 which regulate Islamic inheritance law, and Article 209 which specifically addresses wasiat wajibah. In addition, Law No. 1 of 1974 concerning Marriage serves as the legal framework for family law within the national legal system. The findings indicate that wasiat wajibah is a legal innovation inspired by the principles of justice and protection for relatives whose inheritance rights are otherwise excluded. Article 209 of the KHI explains that there is no inheritance relationship between adopted children and adoptive parents; however, a legal breakthrough exists in the form of wasiat wajibah, which governs such relationships. The transformation of wasiat wajibah into the national legal system is carried out through legislation, judicial practice, and is supported by a legal culture that is increasingly responsive to social justice and the realities of contemporary Muslim families.